Trans-ethnic kidney function association study reveals putative causal genes and effects on kidney-specific disease aetiologies - Morris, A; Le, T; Wu, H; Akbarov, A; Van Der Most, P; Hemani, G; Smith, G; Mahajan, A; Gaulton, K; Nadkarni, G; Valladares-Salgado, A; Wacher-Rodarte, N; et al. (Springer Nature, 2019)
Chronic kidney disease (CKD) affects ~10% of the global population, with considerable ethnic differences in prevalence and aetiology. We assemble genome-wide association studies of estimated glomerular filtration rate (eGFR), a measure of kidney function that defines CKD, in 312,468 individuals of diverse ancestry. We identify 127 distinct association signals with homogeneous effects on eGFR across ancestries and enrichment in genomic annotations including kidney-specific histone modifications. Fine-mapping reveals 40 high-confidence variants driving eGFR associations and highlights putative causal genes with cell-type specific expression in glomerulus, and in proximal and distal nephron. Mendelian randomisation supports causal effects of eGFR on overall and cause-specific CKD, kidney stone formation, diastolic blood pressure and hypertension. These results define novel molecular mechanisms and putative causal genes for eGFR, offering insight into clinical outcomes and routes to CKD treatment development.